Metallic Yielding Dampers and Fluid Viscous Dampers for Vibration Control in Civil Engineering: A Review - Hu, Renkang; Hu, Shangtao; Yang, Menggang; Zhang, Yu (International journal of structural stability and dynamics, 2022)
Structural vibration is a widespread issue occurred in the field of civil engineering. The passive energy dissipation devices are being increasingly popular for protecting structures from external excitations due to their high performance and no need for external energy. They can be divided into displacement-dependent dampers and velocity-dependent dampers, among which the metallic yielding dampers (MYDs) and fluid viscous dampers (FVDs) are the most representative. This paper presents an overview of the MYD and FVD, aiming to reveal their defects and provide suggestions for future development. The basic concept, the mechanical models, the design approaches, and the applications in civil engineering of the two dampers are reviewed. In particular, the obstacles in application and preference in research of these two dampers are summarized, and their merits and drawbacks are further discussed. Emphatically, the strategies for improvement and future development trends are explored.